Functionalization and antioxidant activity of polyaniline–fullerene hybrid nanomaterials: a theoretical investigation. Issue 25 (9th April 2020) - Thong, Nguyen Minh; Vo, Quan V.; Le Huyen, Trinh; Van Bay, Mai; Dung, Nguyen Nho; Thu Thao, Pham Thi; Nam, Pham Cam
Abstract : Functionalized fullerene is one of the most advantageous nanotechnologies to develop novel materials for potential biomedical applications. Abstract : Functionalized fullerene is one of the most advantageous nanotechnologies to develop novel materials for potential biomedical applications. In this study, we applied the ONIOM-GD3 approach to explore the nucleophilic addition reaction mechanism between polyaniline (emeraldine and leucoemeraldine forms) and fullerene. Potential energy surfaces were also analyzed to predict the predominantly formed products of the functionalized reaction. The themoparameters, such as bond dissociation enthalpy (BDE), ionization energy (IE), and electron affinity (EA), characterized by two mechanisms HAT and SET, were used to evaluate the antioxidant activities of the selected compounds. Moreover, the calculated HOMO, LUMO, and DOS results indicate that the electronic structures of polyaniline–fullerene were significantly affected by the presence of fullerene. The computational results show that C60-L1 seems to be the best antioxidant following the SET mechanism.